Analysis of Pollen Collected by Andrena flavipes Panzer (Hymenoptera: Andrenidae) in Sweet Cherry Orchards, Afyonkarahisar Province of Turkey - Yasemin Güler; Kadriye Sorkun (Psyche: A Journal of Entomology)
Andrena, which is the largest genus in the Andrenidae, is a very important genus for the pollination of fruit trees. Andrena flavipes Panzer is one of the most common species observed in the study area and can continue the flight activity even under low temperature. In this study, the pollen collected by A. flavipes was determined. In addition, the potential to carry sweet cherry pollen of the aforementioned species was also researched. For the pollen preparates, the scopae of 34 females were used. As a result of the diagnosis studies, it was determined that A. flavipes species collected the pollens of 13 families and that the dominant pollen group belonged to the Brassicaceae. It was ascertained that A. flavipes collected sweet cherry pollen and that the sweet cherry flowers do not represent a primary pollen source, however.